(untitled) (Anclajes, 2020)
Based on a reading of “No se culpe a nadie” (“Don’t Blame Any-one”) by Cortázar, we have analyzed some strategies used so as to put the passionate dimension into discourse at the enunciation level, taking into con-sideration the relationships between the subjects involved – enunciator and enunciatee – and a particular construction of the utterance as the object. Aspectualization and modal articulations affecting the initial reading con-tract, delaying its execution and generating renewed curiosity in the recep-tor’s simulacrum become pertinent in addressing the relationships between the subjects. Meanwhile, the utterance as the object that circulates is fi lled with meanings that increase the valence of the values assigned to it, cause concern, turn curiosity into expectation and establish suspense as delay, per-plexity and admiration before the text-producing agent’s competence.